1989
DOI: 10.1016/0014-5793(89)80930-5
|View full text |Cite
|
Sign up to set email alerts
|

The primary sequence of the PFK‐1 inactivating zinc‐binding protein as deduced from cDNA sequencing Identity of the zinc‐binding protein with rat parathymosin

Abstract: We have recently described the sequence of the Zn2+-binding domain (43 amino acid residues) of a newly detected Zn 2+-binding protein which reversibly inactivates phosphofructokinase-I in a Zn2+-dependent manner [(1986

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0
10

Year Published

1991
1991
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 14 publications
0
11
0
10
Order By: Relevance
“…This suggests either weak overlap between the FBP11 WW and FBP30 WW binding motifs, which seems unlikely based on the peptide library data in Table I (41). WBP13 represents an out-of-frame fusion with the zinc-binding protein ZnB (42), in which this frame-shifted fusion results in a proline-rich protein. The four remaining sequences (WBP14, WBP15, WBP16, and WBP17) are novel sequences, showing no significant similarity to any known protein in the data base.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests either weak overlap between the FBP11 WW and FBP30 WW binding motifs, which seems unlikely based on the peptide library data in Table I (41). WBP13 represents an out-of-frame fusion with the zinc-binding protein ZnB (42), in which this frame-shifted fusion results in a proline-rich protein. The four remaining sequences (WBP14, WBP15, WBP16, and WBP17) are novel sequences, showing no significant similarity to any known protein in the data base.…”
Section: Resultsmentioning
confidence: 99%
“…Down-regulation of prothymosin mRNA was also observed in an HL-60 myeloid leukemia cell line induced to differentiate with either dimethyl sulfoxide or phorbol 12-myristate 13-acetate (36). In other reports, prothymosin has been shown to be covalently linked to a small cytoplasmic RNA (17), and parathymosin has been identified as the Zn2+-binding protein that reversibly inactivates phosphofructokinase (18).Recent evidence has also raised the possibility of a nuclear site of action for both prothymosin and parathymosin. On the basis of the presence of a "nuclear localization signal" near the COOH terminus ofprothymosin and superficial structural similarities between prothymosin and a variety of nuclear proteins, proposed that it might function as a nuclear protein.…”
mentioning
confidence: 98%
“…Early studies have identified ParaT as a zinc-binding protein, which interacts with several enzymes involved in carbohydrate metabolism (30,31). Recently, ParaT was found to inhibit the binding of the activated glucocorticoid receptor to nuclei, suggesting its involvement in the regulation of glucocorticoid steroids action (32).…”
mentioning
confidence: 99%